Analisis Penerapan Sustainable Development Goals (SDGs) dalam Upaya Peningkatan Pendidikan berkualitas di Indonesia - Magfiroh, Anis; Nugraheni, Nursiwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article analyzes the implementation of Sustainable Development Goals (SDGs) in efforts to enhance quality education in Indonesia. In this context, the research explores the current condition of education in Indonesia, identifies the challenges faced in the education sector, and evaluates efforts made to improve the quality of education. Through an analytical approach, this article discusses the challenges encountered by the Indonesian education system, such as unequal access to education, varying quality of education, and constraints in student development. Additionally, the article reviews various efforts made to enhance quality education, including policies and programs aimed at addressing these challenges. The findings of this analysis can provide valuable insights for policymakers, education practitioners, and other stakeholders to formulate effective strategies in supporting the attainment of education-related Sustainable Development Goals in Indonesia.